2020
DOI: 10.1021/acsbiomaterials.9b01920
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Targeted Anticancer Drug Delivery via a Combination Strategy of a Micelle Complex and Reducible Conjugation

Abstract: Conjugation of various active targeting ligands to the surface of nanocarriers to realize specific recognition by the corresponding receptors localized on the membrane of the cancer cells has provided a powerful means toward enhanced cancer therapy. Folic acid (FA) is one of the most used targeting ligands due to the overexpressed FA receptors in many cancer cell lines. However, conjugation of hydrophobic FA to the surface of nanocarriers usually alters the hydrophilic/hydrophobic balance of the stabilized nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In several reported studies, folate-conjugated drug delivery systems have shown signi cant nuclear uptake. [80][81][82] Folic-acid modi ed silica nanoparticles (FAMSNs) with 100 nm diameter have been observed to accumulate in both the nuclei and the cytoplasm, while unmodi ed MSNs were found only in the cytoplasm, which con rmed the role of folic acid receptors in the nuclear uptake. [81] Presence of folic acid receptor α (FRα) in the nuclear membrane has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In several reported studies, folate-conjugated drug delivery systems have shown signi cant nuclear uptake. [80][81][82] Folic-acid modi ed silica nanoparticles (FAMSNs) with 100 nm diameter have been observed to accumulate in both the nuclei and the cytoplasm, while unmodi ed MSNs were found only in the cytoplasm, which con rmed the role of folic acid receptors in the nuclear uptake. [81] Presence of folic acid receptor α (FRα) in the nuclear membrane has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In several reported studies, folate-conjugated drug delivery systems have shown significant nuclear uptake (Goren et al 1949 ; Porta et al 2013 ; Wang et al 2020 ). Folic acid-modified silica nanoparticles (FAMSNs) with 100 nm diameter have been observed to accumulate in both the nuclei and the cytoplasm, while unmodified MSNs were found only in the cytoplasm, which confirmed the role of folic acid receptors in the nuclear uptake (Porta et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In several reported studies, folate-conjugated drug delivery systems have shown signi cant nuclear uptake. [71][72][73] Folic-acid modi ed silica nanoparticles (FAMSNs) with 100 nm diameter have been observed to accumulate in both the nuclei and the cytoplasm, while unmodi ed MSNs were found only in the cytoplasm, which con rmed the role of folic acid receptors in the nuclear uptake. [72] Presence of folic acid receptor α (FRα) in the nuclear membrane has been reported.…”
Section: Discussionmentioning
confidence: 99%